Smokeless tobacco use and dental care utilization, using a National dataset - R. Constance Wiener (Addictive Behaviors Reports, 2022)
Background: Smokeless tobacco use has serious oral health consequences. The purpose of this current research is to determine the level of dental care utilization among individuals with smokeless tobacco use as compared with individuals who do not use smokeless tobacco. Method: The U.S. national dataset, 2020 Behavioral Risk Factor Surveillance System (BRFSS), was the data source for the cross-sectional study. Smokeless tobacco use and having a dental visit within the previous year were determined from the BRFSS questionnaire. There were 94,821participants included. Chi square and logistic regression analyses were conducted. Results: There was a significant relationship with smokeless tobacco use and not having a dental visit within the previous year even after adjusting for sex, race/ethnicity, age, education, income, health insurance, smoking, and region. The adjusted odds ratio was 1.42 (95 %CI: 1.17, 1.69; p = 0.0002). Conclusion: Individuals who use smokeless tobacco products are less likely to have a dental visit within the previous year.